Radical land reform in South Africa - a comparative perspective? - Jankielsohn, R.; Duvenhage, A. (Faculty of Humanities, University of the Free State, 2017)
A great deal of political rhetoric has been uttered regarding radical economic transformation that includes calls for more radical land reform proposals. This rhetoric is the source of political mobilisation in both the governing African National Congress (ANC), as well as the Economic Freedom Fighters (EFF) opposition. While the ANC call for the end of the willing buyer, willing seller principle in land reform policies and legislation in line with their National Democratic Revolution (NDR), the EFF support a more extreme expropriation without compensation approach. Both these approaches can be regarded as forms of radical land reform that are grounded in their specific ideological orientations. Since no academic definition exists regarding the concept “radical land reform”, it is necessary that this is conceptualised. In order to analyse the possible implications of radical land reform, this article explores the outcomes of similar approaches in the People’s Republic of China (PRC), the former Union of Soviet Socialist Republics (USSR) and Zimbabwe. The lessons of this comparative analysis indicate that land reform requires a balance between existing land rights and food security on the one hand, and the urgency for historical redress and redistribution on the other.
Keywords: Radical land reform; National Democratic Revolution (NDR); African National Congress (ANC); Economic Freedom Fighters (EFF); People’s Republic of China (PRC); Union of Soviet Socialist Republics (USSR); Zimbabwe; Food security; Redistribution; Land reform